Dental students' academic performance before and after the Covid-19 pandemic: A retrospective analysis - Abdulaziz Binrayes; Ahmed Almahdy; Syed Rashid Habib; Abdullah Aljutaili; Yazeed Alotaibi; Sulaiman Aldoihi; Abdulrahman Alkhathran (Elsevier, 2022)
Delivering quality education to students with fair assessment strategies is a key indicator of an excellent educational institution. The present study explored the impact of the COVID-19 pandemic on the academic performance of dental students in terms of the evaluations/grades awarded to them before and during the pandemic. The targeted groups were dental students, studying in the third year of 2018-2019 and 2020-2021 academic years. The sample size included all male and female students who enrolled and completed the following courses: pre-clinical fixed prosthodontics (SDS333), pre-clinical removal prosthodontics (SDS323), clinical operative dentistry-1 (RDS313), and pre-clinical endodontics (RDS323). Evaluations for students who did not complete the requirements were not included in the statistical analysis. Paired sample statistics were used for comparisons between the different groups at p < 0.05. Results revealed statistically significant differences (p ≤ 0.05) for all the course pairs. It was found that students' grades for all the courses during the pandemic year were higher compared to the grades before the pandemic. While female students demonstrated the highest mean difference (6.13) before and during the pandemic year for RDS323, males demonstrated the highest mean difference (8.14) for SDS323. However, both male and female students demonstrated the lowest mean difference (0.25 and 2.03, respectively) for SDS333. The grades were higher during the COVID-19 pandemic. Overall, female students achieved higher grades than male students.